2010
DOI: 10.1111/j.1442-200x.2010.03166.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of food allergy prevalence among Chinese infants in Chongqing, 2009 versus 1999

Abstract: This is the first study in China to indicate time trends in food allergy prevalence and characteristics. Our data show that in the 10-year period from 1999 to 2009, the prevalence of food allergy seems to have increased in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 22 publications
3
89
1
3
Order By: Relevance
“…Fish meat is one of the foods most commonly provoking severe anaphylaxis (Sampson, 2000;Lopata and Lehrer, 2009). There are also a number of reports on anaphylactic reactions to caviar and roe from various fishes (Untersmayr et al, 2002;Makinen-Kiljunen et al, 2003;Flais et al, 2004;Kondo et al, 2005;Escudero et al, 2007;Perez-Gordo et al, 2008;Chen et al, 2009;Gonzalez-De-Olano et al, 2011).…”
Section: Severe Reactions/anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Fish meat is one of the foods most commonly provoking severe anaphylaxis (Sampson, 2000;Lopata and Lehrer, 2009). There are also a number of reports on anaphylactic reactions to caviar and roe from various fishes (Untersmayr et al, 2002;Makinen-Kiljunen et al, 2003;Flais et al, 2004;Kondo et al, 2005;Escudero et al, 2007;Perez-Gordo et al, 2008;Chen et al, 2009;Gonzalez-De-Olano et al, 2011).…”
Section: Severe Reactions/anaphylaxismentioning
confidence: 99%
“…Fish roe-allergic individuals will often tolerate fish (Makinen-Kiljunen et al, 2003;Escudero et al, 2007;Chen et al, 2009). …”
Section: Identified Allergensmentioning
confidence: 99%
“…One study from Chongqing, China, reported a doubling in the challenge-proven prevalence rates from 3.5% to 7.7% among 0-2-year-olds over a ten-year period. (8) Conversely, a South Korean study reported that the prevalence of food allergy symptoms in 6-12-year-olds had decreased from 10.9% to 8.9% over five years.…”
Section: Epid Em Io Lo Gymentioning
confidence: 99%
“…One study from Chongqing, China, reported a doubling in the challenge-proven prevalence rates from 3.5% to 7.7% among 0-2-year-olds over a ten-year period. (8) Conversely, a South Korean study reported that the prevalence of food allergy symptoms in 6-12-year-olds had decreased from 10.9% to 8.9% over five years. (9) Preliminary findings in an ongoing study of young Singaporean children aged 11-30 months demonstrated that overall, self-reported food allergy prevalence could be as high as 5.4% (Lee AJ, unpublished).…”
Section: Epid Em Io Lo Gymentioning
confidence: 99%
See 1 more Smart Citation